2013
DOI: 10.5194/bg-10-6969-2013
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of riverine dissolved organic matter in three Baltic Sea estuaries and the effect of catchment land use

Abstract: Abstract. The microbial degradation of dissolved organic carbon and nitrogen (DOC, DON) was studied in three Finnish boreal estuaries with contrasting land use patterns (Kiiminkijoki -natural forest and peatland; Kyrönjoki -agricultural; Karjaanjoki -mixed/urban). Bioassays of 12-18 d long durations were used in 3 seasons at in situ temperatures. Besides the bulk parameters, a suite of dissolved organic matter (DOM) quality parameters were also investigated, including colored DOM (CDOM), fluorescent DOM and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
120
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 95 publications
(96 reference statements)
15
120
0
Order By: Relevance
“…Indeed, previous studies performed in tropical estuarine waters showed lower BR rates (BR max =0.7 µM C h LEE et al, 2009;RAM et al, 2003). Nutrient availability also plays a major role in regulating bacterial carbon metabolism (ASMALA et al, 2014;BERGGREN et al, 2010;GASOL et al, 2009;KEMP, 2003). Bacterial uptake of DOM follows a rather constant ratio: C:N:P ~ 50:10:1 (FAGERBAKKE et al, 1996;GOLDMAN et al, 1987).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Indeed, previous studies performed in tropical estuarine waters showed lower BR rates (BR max =0.7 µM C h LEE et al, 2009;RAM et al, 2003). Nutrient availability also plays a major role in regulating bacterial carbon metabolism (ASMALA et al, 2014;BERGGREN et al, 2010;GASOL et al, 2009;KEMP, 2003). Bacterial uptake of DOM follows a rather constant ratio: C:N:P ~ 50:10:1 (FAGERBAKKE et al, 1996;GOLDMAN et al, 1987).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the N-NH 4 contents, the most readily available inorganic N form for bacterioplankton (CHURCH, 2008;VALLINO et al, 1996), represented, on average, a minor fraction of total DIN (38%). Inorganic nitrogen limitation of bacterial production and growth efficiency has been widely reported in both batch cultures and natural systems experiments (CARLSSON et al, 2012;CHURCH et al, 2000;KROER, 1993;ORTEGA-RETUERTA et al, 2012), some of them showing a higher dependency of BGE on inorganic nitrogen than on DOM quality (ASMALA et al, 2014;LØNBORG et al, 2011). The direct correlation between BP and N-NH 4 (r=0.53; p=0.01) and the absence of correlation between BP and the N-oxidized forms (r=0.25; p=0.23) suggests a higher reliability of bacterioplankton on ammonium contents in this system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations